ANALYSIS OF FEAR AND ANXIETY FIGURES IN PICTURE STORY BOOKS IN TERMS OF PICTURE AND CONTENT - Hatice UYSAL BAYRAK; Mübeccel Gönen; Neslihan Nur Çelik; Hatice Gökdoğan; Özlem Tütüncü (International Journal of Eurasia Social Sciences, 2017)
In this respect, objective of the study consists of analysis of content and illustration features of fear and anxiety figures in picture story books published in Turkey during the years 2005-2012. In the research, scan descriptive method was used. For the theoretical part of the research, sources were scanned and information was compiled. The study group of the research was determined using appropriate sampling method. 155 book published between 2005 and 2012 in libraries and bookstores of state and private institutions in Ankara were scanned by researchers in order to collect data related to the research and was filled the Picture Story Books Review Form. As a means of collecting data in the research, the Picture Story Books Review Form developed for and was used by the researchers, the purpose of examining the fear and anxiety figures in illustrated children's books. The Picture Story Books Review Form is composed of 33 items with expert opinions taken after the literature is scanned. The first 16 items of the form are based on the general characteristics of the book (title, title, age group, hero, theme, subject matter); the second part relates to the physical characteristics of the book, and the third part deals with the contents of the book. The Picture Story Books that can be reached are read and evaluated according to the form. Five of the books included in the context of study were examined by researchers with a specialist and it is seen that the results are highly consistent between the examiners. Percent and frequency values were calculated and evaluated in the analysis of the data obtained at the end of the study. The findings are discussed in the light of the relevant literature.